STOCK VALUATION OF PT BANK SYARIAH INDONESIA, TBK - Wibowo, Andika Lesmana; Sudrajat, Oktofa Yudha (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
Indonesia is the country with the second largest Muslim population in the world. According to the State of the Global Islamic Economy (SGIE) Report, Indonesia's Islamic market will be the third largest globally by 2023, behind Malaysia and Saudi Arabia. Therefore, to accelerate the halal ecosystem's growth, the government, through the Ministry of State-Owned Enterprises (BUMN), is establishing PT Bank Syariah Indonesia Tbk (BSI). The government through the Ministry of SOEs is encouraging BSI to expand overseas. After opening a branch in Dubai, United Arab Emirates, BSI plans to open a branch in Saudi Arabia soon. Strategic investors are needed for BSI to be able to access the Middle East financial market, especially Saudi Arabia. Investors need information and analysis regarding the potential benefits that will be obtained before deciding to invest in BSI. This study uses qualitative and quantitative methods. The first objective of this study is to compare BSI's performance with the banking industry using the competitor analysis matrix method. Second, to analyze macroenvironmental aspects using the PESTLE and Porter's Five Forces methods. Third, to evaluate BSI shares using the excess return valuation method, asset-based valuation to determine the intrinsic value and relative valuation using the PER and PBV comparison. The results of the competitor analysis matrix study, BSI got a score of 4.61 which means BSI's performance is above the industry average. The intrinsic value of BRIS in the best scenario was IDR 2.949, the moderate was IDR 2.435, and the worst was IDR 2.101. Based on the calculation of intrinsic value using the asset-based model, the resulting intrinsic value is IDR 2.616 per share. The next analysis is relative valuation using the Price-to-earning (P/E) Ratio and price-to-book value (PBV) of PT Bank Syariah Indonesia compared to the industry average. Based on the results of the Monte Carlo simulation, the peak point was obtained at around 2.000–2.500, indicating that most simulation results predict stock prices in this range. The mean value of all simulation results is IDR 2.718. This is the central estimate of the most likely stock valuation in the average scenario. If the current market price is close to this value, the stock can be considered fairly valued. Share price BRIS per 11 Nov 2024 of IDR 2.820 per share, based on simulation upside probability 35%.